Digital Transformation Framework: A Bibliometric Approach - Hajishirzi, Reihaneh (2022)
Hajishirzi, R., Costa, C. J., Aparicio, M., & Romão, M. (2022). Digital Transformation Framework: A Bibliometric Approach. In A. Rocha, H. Adeli, G. Dzemyda, & F. Moreira (Eds.), Information Systems and Technologies: WorldCIST 2022 (Vol. 3, pp. 427-437). (Lecture Notes in Networks and Systems; Vol. 470). https://doi.org/10.1007/978-3-031-04829-6_38 ------------------------ Funding Information: We gratefully acknowledge financial support from FCT Fundação para a Ciência e a Tecnologia (Portugal), national funding through research grant UIDB/04521/2020.